Assessment of an intervention experience using appropriate technologies in Santiago del Estero (Argentina) - Juan Pablo Díaz; Ramiro Rodríguez-Sperat; Raúl Paz (Ciencia y Tecnología Agropecuaria, 2018)
In previous discussions about technological change, appropriate technologies emerged as one of the alternatives to the modernizing technology transfer model that prevailed for many years in Latin America. However, despite the time elapsed since its conceptual creation, it is not easy to find studies assessing interventions carried out with this type of approach. This paper addresses this subject by analyzing a technology transfer experience using goat manure as a fertilizer for household crops in Santiago del Estero (Argentina). Despite having an appropriate a priori design, the technology was not replicated by all the experimenters. A quantitative and qualitative two-stage approach was used to address it: the first approach explored structure variables used by each experimenter and correlated these with the times that he/she repeated the practice; and in the second one, an analysis of the farm operations through case studies was carried out. The results indicate that a particular farm structure did not guarantee a result in terms of adoption of an appropriate technology, and that the operation and the survival strategy (or peasant strategy) of each family gave the farm an individual dynamic that often was decisive in adopting the proposal. In addition, at least for the current experience, technology design using locally controlled resources and the presentation of a unique proposal for all the experimenters was not enough. The multiple adjustments used by peasants suggest the need to investigate local innovation processes.